1998
DOI: 10.1046/j.1523-1747.1998.00171.x
|View full text |Cite
|
Sign up to set email alerts
|

Homozygous R788W Point Mutation in the XPF Gene of a Patient with Xeroderma Pigmentosum and Late-Onset Neurologic Disease

Abstract: The second Caucasian xeroderma pigmentosum patient (XP42RO) belonging to complementation group F (XP-F) is described. Mild ocular photophobia was present from childhood, and acute skin reactions occurred upon exposure to sunlight. Basal and squamous cell carcinomas developed after his twenty-seventh year. In his late forties progressive neurologic symptoms emerged, which included intellectual decline, mild chorea and ataxia, and marked cerebral and cerebellar atrophy. Such neurologic abnormalities are very unu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 27 publications
4
56
0
1
Order By: Relevance
“…In fact, very few XP-F patients have developed skin cancers [see table 3 in Gregg et al (45), but note that contrary to what is indicated in this table, XP24BR and XP32BR have not had any skin cancers]. The few XP-F patients that have developed skin cancers did so as adults (47,48), mostly above the age of 40 y (46,(48)(49)(50). Nevertheless it appears that, whereas XP-C patients have pigmentary changes and skin cancers without abnormally severe sunburn reactions, XP-F patients, in direct contrast, have severe sunburn reactions with only modest pigmentary changes and relatively few skin cancers.…”
Section: Discussionmentioning
confidence: 89%
“…In fact, very few XP-F patients have developed skin cancers [see table 3 in Gregg et al (45), but note that contrary to what is indicated in this table, XP24BR and XP32BR have not had any skin cancers]. The few XP-F patients that have developed skin cancers did so as adults (47,48), mostly above the age of 40 y (46,(48)(49)(50). Nevertheless it appears that, whereas XP-C patients have pigmentary changes and skin cancers without abnormally severe sunburn reactions, XP-F patients, in direct contrast, have severe sunburn reactions with only modest pigmentary changes and relatively few skin cancers.…”
Section: Discussionmentioning
confidence: 89%
“…Neurologic involvement is also seen in some XP-B and XP-D patients [16]. Milder, adult onset neurologic impairment may be seen in XP-C and XP-F patients [17,18]. Neurologic disease has not been reported in XP-E(DDB2) patients [19].…”
Section: Neurological Disease In Xeroderma Pigmentosummentioning
confidence: 99%
“…These patients carry a truncated version of the XPF protein caused by a frame shift mutation that inserts a premature stop codon in front of the ERCC1 binding domain or a point mutation, R788W, which is known to affect heterodimeric complex formation (41). Reduced concentrations of both the XPF and the ERCC1 proteins are observed in these patients, although the genes encoding XPF and ERCC1 are localized to different chromosomes (16).…”
mentioning
confidence: 99%